Technological scheme of the combined geothermal hydrocarbon system for the production and storage of energy resources - Fyk, M. I.; Biletskyi, V. S.; Abbood, M. H.; Fyk, O. I. (My University, 2021)
The complex researches of schemes of extraction and storage of hydrocarbons and geothermal energy are executed in the work. In particular, according to the location, logistics and nature of the processes of generation, transportation, evacuation, injection and local utilization of hydrocarbon and geothermal energy sources, the scheme is divided into subspecies of consumer regional order of electricity, hydrocarbon and chemical energy and hydrogen. It is shown that the tasks of extraction of natural or synthesized hydrocarbons, geothermal energy and subsequent transformation into the required form of commodity resource can be unified with the organization of circuit-combined technologies. At the same time, the developed technological scheme implements the concept of storage of the required amount of energy resources on the one hand and regulation of production capacity for consumption – on the other. The reduction of current energy costs for the implementation and operation of systems with updated functional systems for a total of 20-45%. It is proved that the selection of the scheme of unified extraction and storage energy systems in accordance with the projected order of energy and energy resources, due to the capabilities of productive reservoirs, leads to minimization of capital costs for their construction on a modular basis. Research of application of combined technologies of dual extraction-storage of heat carriers-hydrocarbons is a perspective direction of researches.